Circulating sphingolipids in heart failure - Kovilakath, Anna; Wohlford, George; Cowart, L. Ashley (Frontiers in Cardiovascular Medicine, 2023)
Lack of significant advancements in early detection and treatment of heart failure have precipitated the need for discovery of novel biomarkers and therapeutic targets. Over the past decade, circulating sphingolipids have elicited promising results as biomarkers that premonish adverse cardiac events. Additionally, compelling evidence directly ties sphingolipids to these events in patients with incident heart failure. This review aims to summarize the current literature on circulating sphingolipids in both human cohorts and animal models of heart failure. The goal is to provide direction and focus for future mechanistic studies in heart failure, as well as pave the way for the development of new sphingolipid biomarkers.